2007
DOI: 10.1016/j.virol.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic properties resulting from directed gene segment reassortment between wild-type A/Sydney/5/97 influenza virus and the live attenuated vaccine strain

Abstract: Widespread use of a live-attenuated influenza vaccine (LAIV) in the United States (licensed as FluMist) raises the possibility that vaccine viruses will contribute gene segments to the type A influenza virus gene pool. Progeny viruses possessing new genotypes might arise from genetic reassortment between circulating wild-type (wt) and vaccine strains, but it will be difficult to predict whether they will be viable or exhibit novel properties. To begin addressing these uncertainties, reverse-genetics was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Both groups of inoculated ferrets revealed no virus replication in the lower respiratory tract. This is not unusual, as strain-to-strain variability among human H3N2 viruses with respect to infection of the lower respiratory tract of ferrets has been demonstrated (Jackson et al , 2009; Parks et al , 2007; Svitek et al , 2008; Zitzow et al , 2002). Although the H3N2 MBCS virus was detected in the brain of ferrets, virus titres were very low and virus-infected cells were not detected by immunohistochemistry.…”
Section: Full Textmentioning
confidence: 75%
“…Both groups of inoculated ferrets revealed no virus replication in the lower respiratory tract. This is not unusual, as strain-to-strain variability among human H3N2 viruses with respect to infection of the lower respiratory tract of ferrets has been demonstrated (Jackson et al , 2009; Parks et al , 2007; Svitek et al , 2008; Zitzow et al , 2002). Although the H3N2 MBCS virus was detected in the brain of ferrets, virus titres were very low and virus-infected cells were not detected by immunohistochemistry.…”
Section: Full Textmentioning
confidence: 75%
“…LAIVs are the only vaccines that generate mucosal immunity and are a promising tool in the prevention of IAV-S, but they can replicate in the host and reassortment with field strains cannot be ignored. In fact, reassortment capabilities of LAIVs were demonstrated in experimental conditions and in the field (115,130). Although this reassortment did not result in increased virulence, further research will be needed to evaluate the impact of this process on influenza A virus's epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Parks et al (Parks et al, 2007) reported that reassortant viruses, generated by reverse genetics, derived from a wt H3N2 influenza virus and the corresponding LAIV, were generally no more virulent than the wt H3N2 virus in the ferret model, and, in fact, the data suggested that it is likely that reassortment between the wt and vaccine viruses would result in progeny viruses that would be attenuated compared to the wt virus. The concerns of reassortment with widespread use of a pLAIV prompted us to investigate whether reassortant viruses between candidate pLAIV viruses and contemporary human influenza viruses were viable, and, if so, whether they exhibited a growth advantage and increased virulence in animal models compared to the parent wt human influenza viruses and the candidate pLAIV.…”
Section: Influenza Vaccines Strategiesmentioning
confidence: 99%